A review of the Ptinidae (Coleoptera: Bostrichoidea) of Cyprus, including new faunistic records and the description of a new species - Zahradník, Petr; Demetriou, Jakovos (Zootaxa, 2023)
A review of the Ptinidae (Coleoptera: Bostrichoidea) fauna of Cyprus is presented. A new species, Gastrallus kayiasi sp. nov. is described and compared with other Mediterranean species of the genus Gastrallus Jacquelin du Val, 1860. In addition, 14 species are recorded in Cyprus for the first time, namely: Caenocara affine (Sturm, 1837), Ernobius lenkae Zahradník, 1998 (subfamily Ernobiinae); Dorcatoma (Pilosodorcatoma) chrysomelina Sturm, 1837, Sagetus sp. (subfamily Dorcatominae); Hedobia pubescens (Olivier, 1790) (subfamily Eucradinae); Mesocoelopus niger (P. W. J. Müller, 1821), Mesothes granulatus Pic, 1907 (subfamily Mesocoelopodinae); Ptinus (Bruchoptinus) syriacus Pic, 1896, Ptinus (Ptinus) hirsutus Pic, 1895 (subfamily Ptininae); Lasioderma obscurum (Solsky, 1868), Metholcus rotundicollis Schilsky, 1898, Xyletinus (Xyletinus) subrotundatus Lareynie, 1852, Xyletinus (Xyletinus) sveci Zahradník, 2016 and Xyletinus (Xyletinus) wewalkai Gottwald, 1977 (subfamily Xyletininae). The number of Ptinidae species currently known from Cyprus is raised to 77, distributed in 27 genera in all subfamilies except the Neotropical subfamily Alvarenganiellinae.